Peran Teater Sunda Kiwari dalam Melestarikan Nilai Budaya Sunda di Jawa Barat Melalui Pementasan Teater Tahun 2000-2023 - Shella Gebrilla; Suparman Jassin (UIN Sunan Gunung Djati Bandung, 2025)
This research examines the role of the Sunda Kiwari Theater in efforts to preserve Sundanese culture in West Java from 2000 to 2023. The background to this research is the challenges faced by local culture due to globalization, which can threaten local traditions and values, especially among the younger generation. Globalization often has an influence that can weaken the continuity of local culture, with the younger generation being the group most vulnerable to this erosion. In this context, the Sunda Kiwari Theater functions as a cultural institution that seeks to maintain and promote Sundanese culture through theater arts. The research method used is the historical research method, which consists of four main stages: heuristics, criticism, interpretation, and historiography. The main data was obtained through interviews, documentation and literature review relevant to the history and activities of the Sunda Kiwari Theatre. The results of this research show that the Sunda Kiwari Theater plays a key role in preserving Sundanese culture through theatrical performances that consistently highlight local themes and use Sundanese as the main medium.